The Concept of Wages and Its Application: Analysis of the Ijarah and Ju’alah Contracts in Sharia Economic Institutions - Gojali, Dudang; Iwan Setiawan; Muhamad Izazi Nurjaman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research is motivated by the concept of wages originating from ijarah contracts more widely used in Islamic Economic Institutions than wages derived from ju'alah contracts. While the two contracts are contracts that cause the provision of wages. Therefore, this study will describe the application of the concept of wages to ijarah and ju'alah contracts at the Islamic Economic Institution. This research is a secondary research with a literature study method whose data comes from various literatures through a normative juridical approach. This research is a type of qualitative research with technical data analysis through three stages, namely reducing data, presenting data and drawing conclusions. The results of this study reveal the fact that the concept of wages that is widely used in Islamic economic institutions is wages derived from ijarah contracts. This is because the legal consequences that have the concept of justice are that wages are based on the amount and results that have been completed, rather than wages derived from the ju'alah contract which will be given when a job can be completed perfectly. Therefore, the concept of wages is more identical to the ijarah contract for service benefits, so that there is a development of the meaning of ujrah in the form of wages and rental prices in accordance with the object of the contract exchanged in the ijarah contract.